تأثير نماذج الاتصال والأدوار التنظيمية لشاغلي العلاقات العامة في الصورة الذهنية للمنظمات السورية - صالح, مؤيد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The aim of this research is to study the impact of communication models and the organizational roles of public relations for the practitioners in the brand image of Syrian organizations operating in Damascus. The researcher followed the descriptive analytical methodology to study, describe and analyze the research variables by a questionnaire whose scales were designed and distributed to a sample of /65/ Syrian organizations. The sample was analyzed, and its hypotheses were tested through the statistical program SPSS V.18. The results showed that there was no difference between the averages of the models and the roles of the public relations applied in the Syrian organizations according to the type of organization and according to the scientific certificate. There is also a disparate effect of the communication models and the organizational roles of the public relations Practitioners applied in the Syrian organizations in the brand image of these organizations. The study recommended proposals at the level of models and organizational roles of public relations, and their impact on the brand image of these organizations through the reconstruction of the organizational structures of the public relations departments in order to activate the optimal communication model and harmonize the application of the organizational roles of public relations practitioners. هدف هذا البحث إلى دراسة تأثير نماذج الاتصال والأدوار التنظيمية لشاغلي العلاقات العامة في الصورة الذهنية للمنظمات السورية العاملة في مدينة دمشق. اتبع الباحث المنهج الوصفي التحليلي لدراسة ووصف وتحليل متغيرات البحث من خلال استبانة صممت مقاييسها ووزعت على عينة مكونة من /65/ منظمة سورية وقد حللت إجابات العينة واختبرت فرضيات من خلال البرنامج الإحصائي SPSS V.18 . أظهرت النتائج أن عدم وجود اختلاف بين متوسطات نماذج وأدوار اتصال العلاقات العامة المطبقة في المنظمات السورية وفقاً لنوع المنظمة ووفقاً للشهادة العلمية، كما أن هناك أثر متفاوت لنماذج الاتصال وللأدوار التنظيمية لشاغلي العلاقات العامة المطبقة في المنظمات السورية في الصورة الذهنية لتلك المنظمات. وقد أوصت الدراسة باقتراحات على مستوى نماذج وأدوار اتصال العلاقات العامة وأثرها في الصورة الذهنية لتلك المنظمات من خلال إعادة بناء الهياكل التنظيمية لأقسام العلاقات العامة وذلك لتفعيل نموذج الاتصال الأمثل وتناسق تطبيق الأدوار التنظيمية لشاغلي العلاقات العامة وبما يحقق الأثر المطلوب في الصورة الذهنية للمنظمات السورية.